Improving a fuzzy neural network for predicting storage usage and calculating customer value - Reza Rabieyan; Philipp Pohl (Journal of Revenue and Pricing Management, 2020)
Predicting the behavior of customers plays a crucial role in the quality of resource management and customer services. In this article, a fuzzy neural network model for predicting the customer storage usage is identified. The identified fuzzy neural network is improved and finally the result of the improved fuzzy neural network is compared with some other fuzzy neural network and other prediction methods.
Keywords: 330; Machine learning; Fuzzy neural networks; Resource management; Storage usage; Adaptive second-order algorithm